An integrative system biology approach to delineate complex genotype-phenotype associations in Autism Spectrum Disorder - Asif, Muhammad (2019)
utism Spectrum Disorder (ASD) is a neurodevelopmental disorder which affects the brain structure and the proper establishment of the neuronal connectivity.